Broadband differential interference in a waveguide with a gradient refractive index distribution - Gut, Kazimierz (Photonics Letters of Poland, 2022)
The paper presents a model of a planar broadband differential waveguide interferometer with a gradient refractive index distribution. Its response to the change in the refractive index of the waveguide cover layer is presented. The analysis was performed for the wavelength range from 0.5um to 0.7um. The orthogonal TE0 and TM0 modes propagating in this wavelength range are considered. The influence of the coverage refractive index change on the output characteristics of the system is shown. Full Text: PDF References P. Kozma, F. Kehl, E.Ehrentreich-Forster, C. Stamm and F.F. Bier, "Integrated planar optical waveguide interferometer biosensors: A comparative review", Biosens. Bioelectron. 58, 287 (2014), CrossRef M. Kitsara, K. Misiakos, I. Raptis, and E. Makarona, "Integrated optical frequency-resolved Mach-Zehnder interferometers for label-free affinity sensing", Opt. Express 18, 8193 (2010). CrossRef K. Misiakos, I. Raptis, A. Salapatas, E. Makarona, A. Bostials, et al., "Broad-band Mach-Zehnder interferometers as high performance refractive index sensors: Theory and monolithic implementation", Opt. Express 22, 8856 (2014). CrossRef K. Misiakos, I. Raptis, E. Makarona, A. Botsialas, A. Salapatas, et al, "All-silicon monolithic Mach-Zehnder interferometer as a refractive index and bio-chemical sensor", Opt. Express 22, 26803 (2014) CrossRef K. Misiakos, E. Makarona, M. Hoekman, R. Fyrogenis, K. Tukkiniemi, et al., "All-Silicon Spectrally Resolved Interferometric Circuit for Multiplexed Diagnostics: A Monolithic Lab-on-a-Chip Integrating All Active and Passive Components", ACS Photonics 6, 1694 (2019). CrossRef E. Makarona, A. Salapatas, I. Raptis, P. Petrou, S. Kakabakos, et al., "Broadband Young interferometry for simultaneous dual polarization bioanalytics", J Opt Soc Am B 34, 1691 (2017). CrossRef K. Gut, "Broad-band difference interferometer as a refractive index sensor", Opt. Express 25, 3111 (2017), CrossRef K. Gut, "Study of a Broadband Difference Interferometer Based on Low-Cost Polymer Slab Waveguides", Nanomaterials 9, 729 (2019), CrossRef T. Pustelny, J. Ignac-Nowacka and Z. Opilski, "Optical investigations on layered metalphthalocyanine nanostructures affected by NO2 applying the surface plasmon resonance method", Opt. Appl. 34, 563 (2004). CrossRef W. Lukosz, Sensor Actuat. B-Chem. "Integrated optical chemical and direct biochemical sensors", 29, 37 (1995). CrossRef Z. Qi, S. Xia and N. Matsuda, "Spectropolarimetric interferometer based on single-mode glass waveguides", Opt. Express, 16, 2245 (2008). CrossRef K. Gut, A. Zakrzewski, T. Pustelny, "Sensitivity of Polarimetric Waveguide Interferometer for Different Wavelengths", Acta Phys. Pol. 118, 1140 (2010). CrossRef J.E. Broquin, S. Honkanen, "Integrated Photonics on Glass: A Review of the Ion-Exchange Technology Achievements", Appl.Sci. 11, 4472 (2021). CrossRef G.C. Righini, J. Linares, "Active and Quantum Integrated Photonic Elements by Ion Exchange in Glass", Appl.Sci. 11, 5222 (2021). CrossRef